UJI TOKSISITAS AKUT EKSTRAK DAUN SENDOK (Plantago major) PADA MENCIT(Mus musculus) - Fadholly, Amaq (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
The leaves of Plantago major possess potential mostly for antioxidant, immunostimulant, and laxative properties. The study is to examine the impact of Plantago major leaves extract administration on 25 mice to ascertain the LD50 value in the acute toxicity assessment. Twenty-five female mice were allocated into five groups according to normal control group, negative control group and the dosage of Plantago major leaves extract, with doses of 10, 15, and 20 g/kg body weight. Observations were conducted over a 14-day period, encompassing characteristics such as body weight, physiological responses, clinical symptoms, absolute and relative organ weights, and daily mortality counts. Mortality and clinical signs were examined for 14 days after the treatment. The administration of Plantago major leaves extract to mice did not significantly affect body weight, not absolute or relative organ weight. The collected organs exhibited no severe lesions. The LD50 value of Plantago major leaves extract was determined to be more than 20 g/kg BW. It is concluded that LD50 value is considered as relatively harmless.